Topical anaesthesia degree is reduced in temporomandibular disorders patients: A novel approach to assess underlying mechanisms of the somatosensory alterations. (6th September 2019) - Costa, Yuri Martins; Ferreira, Dyna Mara A. O.; Conti, Paulo César R.; Baad‐Hansen, Lene; Svensson, Peter; Bonjardim, Leonardo R.
Abstract: Background: Changes in quantitative sensory testing (QST) parameters following topical anaesthesia could contribute to better elucidate underlying mechanisms of somatosensory alterations in temporomandibular disorder (TMD) pain patients. This placebo‐controlled crossover investigation compared the somatosensory profile following topical anaesthesia between TMD patients (n = 20) and healthy participants (n = 20). Methods: Cold detection threshold, warm detection threshold, cold pain threshold, heat pain threshold, mechanical detection threshold, mechanical pain threshold, wind‐up ratio and pressure pain threshold were assessed on the skin overlying the masseter at three consecutive days (baseline and immediately after lidocaine 4%/placebo cream). Mixed ANOVA and a coding system that accounts for the diversity of types of peripheral axons associated with the somatosensory parameters were applied for data analysis. Results: The lidocaine application caused no changes in the somatosensory sensitivity in the masseter region in TMD patients ( P  > .050), but sensitivity to cold, cold pain, touch and pinprick stimuli were reduced after topical anaesthesia in healthy participants ( P  < .050). Also, the degree of topical anaesthesia was greater in healthy participants ( P  = .008). The coding system suggested that TMD patients presented only Aδ‐fibre block, whereas a combination of either Aβ‐ and/or C‐fibre block was observed in 35% of healthy participants in addition to Aδ‐fibre block following lidocaine application. Conclusion: Quantitative sensory testing can be successfully applied to identify meaningful differences in the degree of hypoalgesia and hypoesthesia following short‐time topical anaesthesia.